(untitled) (ASEAN Engineering Journal, 2025)
The problem of soft upper soil on port construction leads to several serious issues such as cracking, fracturing, landslides, and structural failure due to consolidation settlement. Moreover, reliably estimating the magnitude of settlement is challenging. Therefore, research towards a more reliable method to predict embankment settlement on soft soil is required. An essential factor in predicting soil settlement is the compression index (Cc). Several researchers have introduced the empirical formula to conduct Cc to generate the optimum prediction of settlement consolidation. However, the appropriate results differ with different formulas in various locations. Kijing Port, located in Pontianak Regency, West Borneo, Indonesia, has a soft soil issue. Fourteen boreholes provided Cc from the laboratory, which divides into three zonas, A, B, and C, with 3-8 settlement plate investigations for each Zona. This paper aims to evaluate consolidation settlement based on Cc using several formulas from empirical equations, field instrumentation monitoring, and laboratory results in the Kijing Port Construction Area. Twenty various empirical formulas were analyzed to obtain the magnitude of settlement, which included soil properties such as void ratio, Atterberg limit, specific gravity and water content, divided into two categories, namely Normally consolidated (NC) and over-consolidated (OC) soil. The results show the different result among the source of Cc due to limited data and other factors like calculation mistakes in the lab, the Cc existing data from the laboratory produces varied values when field investigated from SPT soil sampling. This circumstance suggests that comprehensive soil compression and other important data variables are necessary in order to assure development in the field and to acquire correct soil settlement calculation prediction. The general output is also suggested to generate a comprehensive understanding of the soil compression properties of clay in the port project in West Borneo, Indonesia